Genome-Wide Differentiation of Various Melon Horticultural Groups for Use in GWAS for Fruit Firmness and Construction of a High Resolution Genetic Map - Nimmakayala, Padma; Tomason, Yan R.; Abburi, Venkata L.; Alvarado, Alejandra; Saminathan, Thangasamy; Vajja, Venkata G.; Salazar, Germania; Panicker, Girish K.; Levi, Amnon; Wechter, William P.; McCreight, James D.; Korol, Abraham B.; et al. (Frontiers in Plant Science, 2016)
Melon (Cucumis melo L.) is a phenotypically diverse eudicot diploid (2n = 2x =24) has climacteric and non-climacteric morphotypes and show wide variation for fruit firmness, an important trait for transportation and shelf life. We generated 13,789 SNP markers using genotyping-by-sequencing and anchored them to chromosomes to understand genome-wide fixation indices (Fst) between various melon morphotypes and genomewide linkage disequilibrium (LD) decay. The FST between accessions of cantalupensis and inodorus was 0.23. The FST between cantalupensis and various agrestis accessions was in a range of 0.19 to 0.53 and between inodorus and agrestis accessions was in a range of 0.21 to 0.59 indicating sporadic to wide ranging introgression. The EM (Expectation Maximization) algorithm was used for estimation of 1,436 haplotypes. Average genome-wide LD decay for the melon genome was noted to be 9.27 Kb. In the current research, we focused on the genome-wide divergence underlying diverse melon horticultural groups. A high-resolution genetic map with 7153 loci was constructed. Genome-wide segregation distortion and recombination rate across various chromosomes were characterized. Melon has climacteric and non-climacteric morphotypes and wide variation for fruit firmness, a very important trait for transportation and shelf life. Various levels of QTLs were identified with high to moderate stringency and linked to fruit firmness using both genome-wide association study (GWAS) and biparental mapping. Gene annotation revealed some of the SNPs are located in -D-xylosidase, glyoxysomal malate synthase, chloroplastic anthranilate phosphoribosyltransferase, and histidine kinase, the genes that were previously characterized for fruit ripening and softening in other crops.